Mana, the socio-cultural facets and spatial morphology of Tangale domestic spaces - Maina, Joy (2013)
An increase in population recorded in traditional Nigerian communities facing rapid urbanization created a demand for housing. This has necessitated research regarding the socio-cultural needs of different cultures in the country. This gap is most evident the North East region where little or no intense architectural studies have been carried out in part due to mountainous terrain. Furthermore, no culture specific studies have addressed the relationship between social problems such as insecurity, delinquency and slum environments with changes in lifestyle nor investigate the failure of prototype housing in some of these communities. The present study addresses these issues via two surveys in Tangale land, North East Nigeria. Interdisciplinary approaches combined in ethnography were employed to document the culture and lifestyle of the community for possible relationships between changes in the culture and social problems. Space syntax techniques, scaled drawings and space use patterns were utilized in a measured survey to document and analyse housing in the community. These became instrumental in explaining changes in housing typologies, the sustained use of some socio-cultural values/themes and functional spaces such as courtyards, forecourts for outdoor living as well as spatial and morphological differences between community-produced housing and government-provided prototype units. Results reveal that changes in the culture of the community largely due to external influences are linked to the observed social problems. Four housing typologies and compound transformation patterns also exist in the study area, correlating with four major historical events. Furthermore, the socio-cultural factors of kinship, security and basic needs were not adequately reflected in the design and location of the prototype units which may account for their abandonment and modification. This has implications for future policies in urban planning and architectural design in Tangale land.